2014
DOI: 10.1038/cddis.2014.250
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a natural product-like STAT3 dimerization inhibitor by structure-based virtual screening

Abstract: STAT3 regulates a variety of genes involved with cell proliferation, differentiation, apoptosis, angiogenesis, metastasis, inflammation, and immunity. The purpose of this study was to apply molecular docking techniques to identify STAT3 inhibitors from a database of over 90 000 natural product and natural product-like compounds. The virtual screening campaign furnished 14 hit compounds, from which compound 1 emerged as a top candidate. Compound 1 inhibited STAT3 DNA-binding activity in vitro and attenuated STA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
61
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(64 citation statements)
references
References 67 publications
2
61
0
1
Order By: Relevance
“…41). Using excellent wet chemistry and computer-assisted methods, many compounds have been created that attack this target, several successfully, reducing tyrosine 705 phosphorylation, inhibiting tumor cells in culture, and even effecting a modest inhibition of human tumor xenografts in mice (20,(42)(43)(44)(45). However, no molecule has been devised or unearthed that has adequate specificity and pharmacologic efficacy to provide hope that this obvious anticancer target will soon yield an effective anti-STAT3 drug in humans.…”
Section: Discussionmentioning
confidence: 99%
“…41). Using excellent wet chemistry and computer-assisted methods, many compounds have been created that attack this target, several successfully, reducing tyrosine 705 phosphorylation, inhibiting tumor cells in culture, and even effecting a modest inhibition of human tumor xenografts in mice (20,(42)(43)(44)(45). However, no molecule has been devised or unearthed that has adequate specificity and pharmacologic efficacy to provide hope that this obvious anticancer target will soon yield an effective anti-STAT3 drug in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Computer screening proved to be effective in the identification of new STAT3 SH2 domain binding inhibitors, blocking STAT3 dimerization, including some well-known compounds like STA-21 9 , S3I-201 10 and STX-0119 11 , which have been all identified through in silico screening purely relied on the docking of compound libraries into the STAT3 SH2 domain. Other examples of docking-based virtual screening (VS) studies are reported in literature [12][13][14][15] and recently some fragment-based drug design studies, combining docking and synthesis, have been published 16,17 . However, different computational approaches, like QSAR studies and pharmacophore screening, have been rarely applied 18,19 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that molecular docking, pharmacophore modeling, and structure-based virtual screening in drug discovery have been successful applied. Structure-based virtual screening has emerged as an efficient strategy in identifying potential a natural product-like STAT3 dimerization inhibitor from a database of natural product and natural product-like compounds, and molecular docking analysis suggested that compound 1 might putatively function as an inhibitor of STAT3 dimerization by binding to the SH2 domain [21]. The novel TLR1-TLR2 inhibitors were obtained through molecular docking from a database of natural product and natural product-like compounds and the results of activity experiments show that compound 1 was the most effective in inhibiting TNF-a and IL-6 secretion induced by Pam3CSK4 in RAW 264.7 cells [22].…”
Section: Introductionmentioning
confidence: 99%